PATUNG SEBAGAI MEDIA REKAM JEJAK TRANSFORMASI POLITIK, SOSIAL, DAN BUDAYA DALAM MUSEUM LIMA GUNUNG: STATUE AS A MEDIUM FOR DOCUMENTING POLITICAL, SOCIAL, AND CULTURAL TRANSFORMATIONS IN MUSEUM LIMA GUNUNG - Luqman Wahyudi; Sunarmi; Sarwanto (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2025)
This article discusses the role of sculpture as a medium for documenting political, social, and cultural transformations at the Lima Gunung Museum. The sculptures in this museum not only represent visual beauty, but also function as symbolic reflections on socio-political issues. Case studies of works such as Gus Semar Gunung, Cocot Kencono, Cicak vs Buaya, and Sinar Hati Gus Dur present critiques of phenomena such as pluralism, the post-truth era, power conflicts, and cultural acculturation. Through an aesthetic analysis approach based on AA Djelantik's theory, this article shows how sculpture can be a documentation tool that preserves historical narratives visually, conveys universal social criticism, and triggers dialogue with audiences. Documentation through sculpture provides an important contribution to understanding the dynamics of Indonesian society and politics, making art a bridge between aesthetic values ​​and social messages.